Skeletal muscle (BioMed Central Ltd., 2011)
A peer-reviewed, open access, online journal that publishes articles investigating molecular mechanisms underlying the biology of skeletal muscle. A wide range of skeletal muscle biology is included: development, metabolism, the regulation of mass and function, aging, degeneration, dystrophy and regeneration. The emphasis is on understanding adult skeletal muscle, its maintenance, and its interactions with non-muscle cell types and regulatory modulators.